2006
DOI: 10.1007/s10311-006-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of textile dyes from water by the electro-Fenton process

Abstract: International audienceAn environmentally friendly electrochemical treatment, electro-Fenton process, was applied to the depollution of a synthetic dismissal composed of three dyes, yellow drimaren, congo red and methylene blue, frequently used in textile and dyehouses. Here, we show that those dyes and their mixture are quickly degraded under current controlled electrolysis conditions, leading to an almost complete mineralization. The results show the efficiency of electro-Fenton process to quickly degrade aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(41 citation statements)
references
References 12 publications
3
38
0
Order By: Relevance
“…This value is in agreement with k abs values for hydroxylation reactions of aromatic compounds with hydroxyl radicals [47][48][49]. No absolute rate constant of hydroxylation of DO 61 was found in literature for comparison.…”
Section: Time -Concentration B13supporting
confidence: 85%
See 1 more Smart Citation
“…This value is in agreement with k abs values for hydroxylation reactions of aromatic compounds with hydroxyl radicals [47][48][49]. No absolute rate constant of hydroxylation of DO 61 was found in literature for comparison.…”
Section: Time -Concentration B13supporting
confidence: 85%
“…We have chosen, at first, the approach of Doehlert [48]. Indeed, these designs are formed by uniformly distributed points within the space of the coded variables (X i ).…”
Section: Optimal Conditions For the Mineralization Of Do 61mentioning
confidence: 99%
“…On the other hand, Oturan et al reported that the mineralization efficiency values were higher than 90% for CF cathode by optimizing experimental conditions (larger electrode surface, higher applied current (300 mA), longer electrolysis time, etc.) in several cases [ 11,22,[27][28][29]. The residual TOC of the system arises from the formed carboxylic acids and particularly oxalic acid during the mineralization of BB3.…”
Section: Efficiency Of Cs and Cf Electrode In The Degradation And Minmentioning
confidence: 99%
“…Recalcitrant textile wastewater typically contains high concentrations of organic compounds [expressed as high chemical oxygen demand (COD)], colors associated with residual dyes, a wide range of pH, low biodegradability, and high salt content (Balcioglu and Arslan 1997, Lahkimi et al 2006, Schrank et al 2007, Hassan et al 2009, Rodrigues et al 2009, Blanco et al 2012, Hammami et al 2012, Punzi et al 2012. The characteristics of textile wastewater are depicted in Table 2.…”
Section: Characterization Of Textile Wastewatersmentioning
confidence: 99%